2002
DOI: 10.1029/2002gl015142
|View full text |Cite
|
Sign up to set email alerts
|

How sharp is the tropopause at midlatitudes?

Abstract: [1] Ten years of high-resolution radiosonde data are contrasted with fifteen years of ECMWF reanalysis (ERA) data to explore the tropopause region above two midlatitude stations (Munich and Stuttgart) in Southern Germany. We present time-averaged vertical profiles of several meteorological parameters relative to the tropopause. A strong mean inversion at the tropopause is evident from the radiosonde profiles with a vertical extension of about 2 km and a temperature increase of about 4 K. The impact of the trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
242
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(271 citation statements)
references
References 18 publications
18
242
0
2
Order By: Relevance
“…In order to clearly separate tropospheric and stratospheric air we transform the data to a tropopause-based vertical coordinate, chosen as the distance to the local tropopause in potential temperature before calculating all averages (for using this method in a different context, see, e.g., Birner et al, 2002;Hoor et al, 2004). The distributions in the monsoon region change substantially when viewed in tropopausebased coordinates along a surface at 10 K above the local tropopause (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to clearly separate tropospheric and stratospheric air we transform the data to a tropopause-based vertical coordinate, chosen as the distance to the local tropopause in potential temperature before calculating all averages (for using this method in a different context, see, e.g., Birner et al, 2002;Hoor et al, 2004). The distributions in the monsoon region change substantially when viewed in tropopausebased coordinates along a surface at 10 K above the local tropopause (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Vertical transport through the tropopause is inhibited by a strong gradient in static stability (cf. Birner, 2002;Pan et al, 2004), whereas quasi-horizontal transport along isentropes near the tropopause is inhibited by a strong meridional PV gradient (cf. Birner, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Pan et al, 2004). A tropopause based climatology of high-resolution radiosonde data by Birner et al (2002) revealed that static stability exhibits a distinct maximum just above the extratropical tropopause, a feature not reproduced in ECMWF data which are used in the here presented study. However, the existence of the maximum in static stability and the coincident gradient in the tracer observations highlight the role of the tropopause to act as a transport barrier.…”
Section: Median Tracer Distributions In (φ E ) Coordinatesmentioning
confidence: 99%
“…Most of the contrails form in the upper troposphere or lower stratosphere where strong winds, shear and stratification prevail (Birner et al, 2002;Houchi et al, 2010;Manney et al, 2011). Shear production of turbulence is driven by total shear S T , while plume distortion follows the vertical shear S of the plume-normal velocity,…”
Section: The Turbulence Modelmentioning
confidence: 99%